Powdered acetylene black material, its manufacturing method, and compositions, articles of manufacture and uses thereof
Patent Information
- Application Number
- JP2023571456
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-05-18
- Filing Date
- 2022-05-17
- Publication Date
- 2025-04-01
Abstract
Description
[Technical field]
[0001] The present invention relates to a process for the preparation of a powdered acetylene black material, to the powdered acetylene black material obtainable thereby, and to compositions containing it, as well as to articles made therefrom, and to the uses and applications of the powdered acetylene black material, e.g. for the manufacture of electrodes or other components of energy storage or conversion devices, rubber articles or plastic articles. [Background technology]
[0002] Acetylene black is a specific type of carbon black, which can be obtained by pyrolysis of acetylene gas or acetylene-containing hydrocarbon feedstocks to form colloidal carbon black particles and hydrogen at high temperatures. Acetylene black has unique properties that distinguish it from other types of carbon black, such as furnace black. Thus, due to the manufacturing process, which involves clean feedstocks and does not require oxidizing agents, acetylene black is generally very pure, has a relatively high structure and degree of graphitization compared to other types of carbon black, and has excellent conductivity. These properties make acetylene black particularly interesting as an electrical and / or thermal conductive agent. It is therefore widely used, for example, in the manufacture of batteries, fuel cells, capacitors or heating elements, as well as to provide antistatic, heat dissipation or conduction properties. In addition, acetylene black is sometimes utilized to impart reinforcement and / or coloring to plastic or rubber articles, such as tires and their parts, such as tires, bladders, cables, conveyor belts, rollers, hoses, flooring, or shoes, or electronic components, paints, ink coatings, and adhesives.
[0003] Acetylene black is conventionally obtained as a fluffy powder with low bulk density. Due to the substantial absence of polar functional groups on the surface of the particles, acetylene black is also generally very hydrophobic and exhibits low hygroscopicity. However, the low density fluffy morphology and hydrophobic nature of acetylene black cause difficulties in incorporating acetylene black into other materials. For example, acetylene black often has to be finely and uniformly dispersed in more or less polar materials, such as plastic or rubber materials or liquid carrier media, for example in the manufacture of plastic or rubber articles, or in the preparation of aqueous or solvent-based compositions for the manufacture of electrodes, coatings, paints or inks, etc. The low density fluffy morphology and hydrophobic nature of acetylene black promote the suspension, aggregation and agglomeration of carbon black particles, thereby promoting the segregation of carbon black particles from the matrix, which works against the fine and uniform dispersion of carbon black particles in the respective matrix, making obtaining a suitable dispersion a demanding and elaborate task. Additionally, dispersions of acetylene black tend not to be stable over time, which can lead to undesirable variations in the properties of the final product.
[0004] Thus, there is a continuing need for acetylene black that has improved dispersibility and that allows for the efficient formation of suitable dispersions that are stable over time, ideally without adversely affecting other properties of the acetylene black that are relevant to the intended application, while preserving the powder morphology familiar to customers and allowing the use of established processing and existing equipment.
[0005] It is therefore an object of the present invention to provide an acetylene black which overcomes or mitigates at least some of the above-mentioned deficiencies and limitations of the prior art. In particular, it is an object to provide a powdered acetylene black material which can be more easily and efficiently dispersed, resulting in high quality dispersions which are stable over extended periods of time, and where possible, maintaining or even improving other beneficial properties of acetylene black, such as its conductivity-imparting properties. Moreover, for ease of implementation, the acetylene black should be obtainable in an economical manner which is compatible with conventional acetylene black manufacturing means. Summary of the Invention
[0006] This object and the additional advantages described herein have been unexpectedly achieved by providing a process for producing a powdered acetylene black material as defined in the attached independent claim 1.
[0007] Accordingly, the present invention relates to a method for producing a powdered acetylene black material, the method comprising: Providing an initial acetylene black; densifying the initial acetylene black provided to form a densified acetylene black; and pulverizing the densified acetylene black to form a powdered acetylene black material.
[0008] The present invention also relates to a powdered acetylene black material obtainable by the process according to the invention as disclosed above and described in more detail below.
[0009] The present invention further relates to compositions comprising such powdered acetylene black material, the preparation of such compositions, and articles made therefrom, in particular electrodes or other components of energy storage and / or conversion devices, and rubber or plastic articles.
[0010] Furthermore, the present invention relates to the use of the powdered acetylene black material disclosed herein as an electrical conductor, antistatic agent, thermal conductive agent, reinforcing filler and / or colorant for the manufacture of electrodes and other components of energy storage and / or conversion devices such as, for example, primary batteries, secondary batteries, fuel cells and capacitors, and / or for the manufacture of plastic articles made of thermoplastic or thermoset polymer or rubber matrix such as tires, wires, cable sheaths, belts, hoses, shoe soles, rollers, heaters or bladders, and / or in coatings, paints or inks.
[0011] The powdered acetylene black obtained according to the process disclosed herein offers several advantages. Thus, the acetylene black according to the present invention exhibits improved dispersibility, resulting in stable dispersions over extended periods of time. Compositions having good processability, including, for example, electrode pastes, can be formed using the acetylene black according to the present invention. The acetylene black according to the present invention maintains or even enhances the beneficial properties of acetylene black, such as its high purity and electrical conductivity, and can be obtained in an economical manner that is compatible with conventional acetylene black manufacturing means. The acetylene black according to the present invention can be provided to customers in a familiar powder form and can be used in established processes using existing equipment.
[0012] These and other optional features and advantages of the present invention are explained in greater detail in the following description. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] As used herein, the term "comprising" is understood to be open-ended and not excluding the presence of additional elements, materials, components or method steps, etc., not described or listed. The terms "including," "containing," and similar terms are understood to be synonymous with "comprising." As used herein, the term "consisting of" is understood to exclude the presence of any unspecified elements, components, or method steps, etc.
[0014] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.
[0015] Unless otherwise indicated, the numerical parameters and ranges set forth in the following specification and appended claims are approximations. Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the invention are approximations, the numerical values set forth in the specific examples are reported as precisely as possible. Any numerical values, however, contain errors necessarily resulting from the standard deviation in their respective measurements.
[0016] It is also to be understood that any numerical range recited herein is intended to encompass all subranges subsumed therein, for example, a range of "1 to 10" is intended to encompass any and all subranges between and including the recited minimum value of 1 and the recited maximum value of 10, i.e., all subranges beginning with a minimum value of 1 or greater and ending with a maximum value of 10 or less, for example, all subranges between 1 to 6.3, or 5.5 to 10, or 2.7 to 6.1.
[0017] All parts, amounts, concentrations, etc. referred to herein are by weight unless otherwise specified.
[0018] As noted above, the present invention relates to a method for producing a powdered acetylene black material, the method including providing an initial acetylene black, densifying the provided initial acetylene black to form densified acetylene black, and pulverizing the densified acetylene black to form a powdered acetylene black material.
[0019] The initial acetylene black utilized as starting material for producing the powdered acetylene black material of the present invention can be provided by any suitable method. The production of acetylene black is well known per se in the art and is reviewed, for example, in J.-B. Donnett et al., Carbon Black: Science and Technology, 2nd Edition, and will not be described in further detail here. Thus, the initial acetylene black can be produced in a reactor from a feedstock containing acetylene, such as acetylene gas or an acetylene-containing hydrocarbon feedstock, as described, for example, in JP 56-90860 A or U.S. Pat. No. 2,475,282 A. Acetylene black is typically formed by pyrolysis of an acetylene-containing feedstock. The pyrolysis of the acetylene-containing feedstock to form colloidal carbon black particles and hydrogen occurs at high temperature in a reactor. The temperature for pyrolysis of the acetylene feedstock may, for example, be at least 1,500° C., such as 2,000° C.
[0020] Acetylene black obtained by such an acetylene black process is commercially available from a number of manufacturers, such as Orion Engineered Carbons, Denka, Hexing Chemical Industry, or Phillips Carbon Black, and can be utilized as the starting material for producing the powdered acetylene black material of the present invention.
[0021] The initial acetylene black provided as a starting material for producing the powdered acetylene black material of the present invention may have one or more or all of the characteristics described below.
[0022] Thus, the initial acetylene black can be characterized by its specific surface area. The initial acetylene black can be, for example, 20 m 2 / g or more, e.g. 30m 2 / g or more, 40m 2 / g or more, 50m 2 / g or more, or 60m 2 The initial acetylene black can have a BET surface area of 200 m 2 / g or less, e.g. 180m 2 / g or less, 160m 2 / g or less, 140m 2 / g or less, 120m 2 / g or less, or 100m 2 The BET surface area of the initial acetylene black can be 20 m 2 / g~200m 2 / g, 40-140m 2 / g, or 60-100m 2 The BET surface area may range between any of the recited values, such as 1 / g. The BET surface area measured may be measured by nitrogen adsorption according to ASTM D6556-19a.
[0023] Additionally or alternatively, the initial acetylene black can be characterized by its oil absorption number (OAN) measured according to ASTM D2414-19. The initial acetylene black can have, for example, an OAN of 500mL / 100g or less, such as 450mL / 100g or less, 400mL / 100g or less, 350mL / 100g or less, or 300mL / 100g or less. The initial acetylene black can have, for example, an OAN of 50mL / 100g or more, such as 100mL / 100g or more, 150mL / 100g or more, 200mL / 100g or more, or 250mL / 100g or more. The OAN of the initial acetylene black can range between any of the listed values, such as 50 mL / 100 g to 500 mL / 100 g, 100 mL / 100 g to 400 mL / 100 g, or 150 mL / 100 g to 300 mL / 100 g.
[0024] Further, additionally or alternatively, the initial acetylene black can be characterized by the oil absorption of a compressed sample (COAN) measured according to ASTM D3493-19a. The initial acetylene black can have, for example, a COAN of 300 mL / 100 g or less, such as 250 mL / 100 g or less, 200 mL / 100 g or less, or 150 mL / 100 g or less. The initial acetylene black can have, for example, a COAN of 50 mL / 100 g or more, such as 100 mL / 100 g or more, 120 mL / 100 g or more, or 140 mL / 100 g or more. The COAN of the initial acetylene black can range between any of the listed values, such as 50 mL / 100 g to 300 mL / 100 g, or 100 mL / 100 g to 200 mL / 100 g.
[0025] Further, additionally or alternatively, the initial acetylene black can be characterized by an acetone absorption number measured according to Indian Standard IS12178-1987, test method A-6. Thus, the initial acetylene black can have, for example, an acetone absorption number of 5 mL / 5g or more, such as 10 mL / 5g or more, 15 mL / 5g or more, 25 mL / 5g or more, or 30 mL / 5g or more. The initial acetylene black can have, for example, an acetone absorption number of 100 mL / 5g or less, such as 80 mL / 5g or less, 70 mL / 5g or less, 60 mL / 5g or less, 50 mL / 5g or less, or 40 mL / 5g or less. The initial acetylene black can have an acetone absorption number in the range between any of the listed values, such as 5 mL / 5g to 100 mL / 5g, 15 mL / 5g to 80 mL / 5g, or 25 mL / 5g to 40 mL / 5g.
[0026] Additionally or alternatively, the initial acetylene black can be characterized by its chemical composition or purity, for example by its carbon content, sulfur content, iron content and / or ash content. For example, the initial acetylene black can have a carbon content of 90% by weight or more, for example 95% by weight or more, or 98% by weight or more, preferably 99% by weight or more, more preferably 99.5% by weight, based on the total weight of the initial acetylene black. The sulfur content of the initial acetylene black can be, for example, 1% by weight or less, for example 0.5% by weight or less, or 0.2% by weight or less, preferably 0.1% by weight or less, more preferably 0.05% by weight or less, based on the total weight of the initial acetylene black. The carbon content and sulfur content can be measured by quantitative elemental analysis. The initial acetylene black can have a low metal content, in particular a low iron content. The iron content of the initial acetylene black can be, for example, 1000 ppm or less, for example, 500 ppm or less, 200 ppm or less, 100 ppm or less, 50 ppm or less, or 20 ppm or less, preferably 10 ppm or less, more preferably 5 ppm or less, based on the total weight of the initial acetylene black. The metal content or iron content of the acetylene black can be measured by inductively coupled plasma optical emission spectroscopy (ICP-OES). Furthermore, the initial acetylene black can have an ash content of 1 wt. % or less, for example, 0.5 wt. % or less, 0.2 wt. % or less, preferably 0.1 wt. % or less, more preferably 0.05 wt. % or less, based on the total weight of the acetylene black. The ash content can be measured according to ASTM D1506-15.
[0027] In the process for producing the powdered acetylene black material of the present invention, as starting materials, an individual acetylene black or a mixture or combination of multiple (two or more) acetylene blacks, such as those having the above characteristics, can be used.
[0028] The initial acetylene black is typically provided in the form of a fluffy powder. The initial acetylene black as provided may have, for example, a bulk density of 50 g / L or less, such as 40 g / L or less, 35 g / L or less, or 30 g / L or less. Bulk density may be measured according to ASTM D1513-05.
[0029] As mentioned above, the initial acetylene black provided is densified in the process according to the invention to form densified acetylene black. Densification refers to rendering the initial acetylene black into a denser form, i.e., a form having a greater specific weight. For example, acetylene black initially provided in the form of a fluffy powder can be densified to form compacted bodies, pellets, granules, etc., derivable therefrom. Densification can be carried out by any method known in the art for densifying powdered materials, such as, but not limited to, compaction, rolling, pelletizing, granulation, briquetting, or combinations thereof. Densification of the initial acetylene black can be carried out using conventional techniques and equipment, including, for example, fluidized bed spray granulation, fluidized spray drying, and agitation granulation equipment such as a pin mixer granulator or a ring bed mixer granulator, whereby, in accordance with the present invention, a ring bed mixer granulator is preferably used. In the preferred practice of the present invention, densification comprises pelletizing the initial acetylene black to form pelletized acetylene black. Generally, any method of pelletizing carbon black known in the art can be utilized, such as dry pelletizing, wet pelletizing, or a combination thereof, with wet pelletizing being preferred. The pelletization of the initial acetylene black can be carried out, for example, as described in EP 2913368 B1.
[0030] In wet pelleting, the initial acetylene black to be pelletized is contacted with a pelleting liquid to form wet pellets, which may then be dried. The pelleting liquid may include water and / or one or more organic solvents. Advantageously, the pelleting liquid is volatile at relatively low temperatures, such as 150° C., facilitating drying of the wet pellets in an economical manner. Suitable organic solvents include, for example, alcohols, ketones, aldehydes, esters, ethers, carboxylic acids, hydrocarbons, or mixtures or combinations thereof, with alcohols, such as ethanol or isopropanol, being preferred. Acids and / or bases, such as hydrochloric acid, sulfuric acid, phosphoric acid, or alkali hydroxides, may further be used in the pelleting liquid to adjust the pH. Pelletizing the initial acetylene black to form pelletized acetylene black may be carried out as a wet pelleting process, in particular using an aqueous medium, such as water, or a mixture of water with one or more organic solvents, such as alcohols, such as ethanol and / or isopropanol. An aqueous medium, as used herein, refers to a liquid medium that contains more than 50% water by weight, based on the total weight of the liquid medium.
[0031] For wet pelleting, the pelleting liquid, such as an aqueous medium as described above, can be used in an amount of 50% by weight or more, e.g., 60% by weight or more, 70% by weight or more, or 75% by weight or more, based on the total weight of the acetylene black and the pelleting liquid. The pelleting liquid can be used, for example, in an amount of 95% by weight or less, e.g., 90% by weight or less, 85% by weight or less, or 80% by weight or less, based on the total weight of the acetylene black and the pelleting liquid. The pelleting liquid can be used in an amount between any of the recited values, such as 50% by weight to 95% by weight, or 70% by weight to 90% by weight, based on the total weight of the acetylene black and the pelleting liquid. The pelleting liquid can be added to the acetylene black at different stages of the wet pelleting process, such as before or after the acetylene black is introduced into, for example, a ring bed mixer granulator.
[0032] Densification, such as (wet) pelleting, can be carried out at elevated temperatures above ambient temperature (20°C). For example, densification, such as (wet) pelleting, can be carried out at temperatures of 30°C or higher, such as 40°C or higher, or 50°C or higher. It can be carried out at temperatures of 90°C or lower, such as 80°C or lower, or 70°C or lower. Densification, such as (wet) pelleting, can be carried out at a temperature range between any of the listed temperatures, such as 30°C to 90°C, or 40°C to 80°C. Heating to such elevated temperatures can be achieved by heating means implemented in the equipment used for densification, such as a ring bed mixer granulator. Additionally or alternatively, the pelleting liquid can be heated before mixing with the acetylene black. For example, the pelleting liquid can be heated to a temperature as described above.
[0033] In the methods disclosed herein, the densification of the initial acetylene black can be carried out in a single densification step or in multiple densification steps, for example, two or more densification steps. For example, pelletizing the initial acetylene black can include two or more wet pelletizing steps, or a combination of dry and wet pelletizing steps. Thus, the individual pelletizing steps can be carried out applying the same or different process parameters in the different densification steps, as described above.
[0034] In the step of densifying the initial acetylene black, for example by dry or wet pelletizing, one or more additives can be optionally used. Thus, at least one additive can be used in the step of densifying the initial acetylene black in the presence of a liquid medium and / or in a dry state. In the case of wet pelletizing, the one or more additives can be provided, for example, together with the pelletizing liquid, for example as a mixture, or can be added separately to the initial acetylene black before and / or during the densification process, for example before or after it is introduced into the agitation granulator. Additionally or alternatively, one or more additives can also be added to the formed densified acetylene black before pulverization. Suitable additives include, for example, dispersants and / or polymers.
[0035] Dispersants as understood herein refer to substances that aid in dispersing the powdered acetylene black in the carrier medium. Dispersants as defined herein may also be referred to in the literature as surfactants, wetting agents, surfactants, etc. Dispersants that may be used in accordance with the present invention include any dispersants commonly used in the art, including ionic, nonionic and amphoteric dispersants. Non-limiting examples of suitable ionic dispersants include (poly)phosphates, silicates, citrates, polyacrylates and carboxylates, for example in the form of alkali metal and ammonium salts, organic phosphates such as alcohol phosphates, organic sulfates such as sodium alkyl sulfates, sodium alkyl sulfonates, organic sulfonates such as formaldehyde naphthalene sulfonates, dioctyl ester sodium sulfosuccinate and sulfonated lignin, as well as anionic and cationic dispersants such as trimethylhexadecyl ammonium chloride. Suitable nonionic dispersants include organic amines such as alkanolamides, such as the condensation products of fatty acids with alkanolamines (monoethanolamine, diethanolamine, monoisopropanolamine, etc.), organic esters such as sorbitan laurate and sorbitan stearate, lanolin, ethoxylated octylphenol, and phospholipids such as lecithin.Suitable nonionic dispersants also include polymers such as polyvinylpyrrolidone, polyesters, polyethers such as glycols (including polyethylene glycol (PEO), polypropylene glycol (PPO), and derivatives such as the reaction products of PEO and PPO with, for example, alkanols and sorbitan stearate), and copolymers such as polyethylene glycol / polypropylene glycol copolymers.
[0036] The polymers that can be used as additives within the scope of the present invention are not particularly limited, and include all kinds of polymeric materials used in the art, in addition to the above-mentioned polymeric dispersants.Non-limiting examples include polymeric binders, such as waxes, such as carnauba wax and beeswax, colophonium resins, sugars, such as agarose and molasses, lignin sulfonates, celluloses, such as sodium carboxymethylcellulose, and starch.Further examples include synthetic polymers and resins, such as polyesters, acrylics, epoxies, melamine formaldehyde resins, phenolic resins, polyurethanes, polyamides, and vinyl esters.
[0037] The optional additive(s), if used, may be used in any suitable amount. Typically, the one or more additives are used in a total amount of 30 wt% or less, e.g., 20 wt% or less, or 10 wt% or less, based on the total weight of the acetylene black and additives. The one or more additives may, for example, be used in a total amount of 0.1 wt% or more, e.g., 0.5 wt% or more, 1 wt% or more, or 2 wt% or more, based on the total weight of the acetylene black and additives. The additive(s), if any, may be used in a total amount between any of the recited values, such as 0.1 wt% to 30 wt%, or 1 wt% to 10 wt%, based on the total weight of the acetylene black and additives. The one or more additives, if used, are preferably incorporated into the formed powdered acetylene black material.
[0038] The process of the present invention may optionally include degassing the initial acetylene black before and / or during the densification step. Degassing allows for the removal of air that may be present in the material to be densified, for example between the acetylene black particles. Degassing can be carried out by any method known in the art for degassing powders. Typically it involves applying a vacuum.
[0039] The process according to the invention may optionally further comprise drying the acetylene black, for example after the densification step and / or after the micronization step. Drying may be particularly useful when the acetylene black is contacted with a wetting medium, for example in a wet pelletization step, followed by removal of residues of the wetting medium, such as the pelletization liquid, from the acetylene black. Drying may be carried out by drying means commonly used in the art, for example by applying heat and / or reduced pressure. Drying may include exposing the acetylene black to be dried to a temperature at which the wetting medium to be removed, such as water and / or organic solvents, has a significant vapor pressure. For example, the acetylene black to be dried may be heated to a temperature of 30° C. or higher, for example 50° C. or higher, 75° C. or higher, 100° C. or higher, or 150° C. or higher. Drying may be accomplished in or by equipment also utilized for densification, such as a one-pot processor or a fluidized spray granulator. Drying may also be carried out in a separate apparatus, such as a rotary dryer or oven. Drying may be carried out under a controlled atmosphere, such as in air, under an inert gas atmosphere, or under vacuum. For example, the acetylene black can be dried such that the residual moisture content of the acetylene black, e.g., densified acetylene black, after drying is less than 1 wt.%, e.g., less than 0.5 wt.%, less than 0.1 wt.%, or less than 0.05 wt.%, based on the total weight of the acetylene black. Moisture content can be measured according to ASTM D1509-95.
[0040] By densifying the initial acetylene black provided, densified acetylene black is formed, which may optionally be dried as described above. The densified acetylene black thus has a denser morphology compared to the initial acetylene black. For example, the densified acetylene black may have the form of a compressed entity such as pellets or granules. The densified acetylene black may have a bulk density of, for example, at least 100 g / L, at least 120 g / L, at least 140 g / L, at least 160 g / L, or at least 180 g / L. The densified and optionally dried acetylene black may have a bulk density of, for example, 260 g / L or less, 240 g / L or less, 220 g / L or less, or 200 g / L or less. The bulk density of the densified and optionally dried acetylene black can range between any of the listed values, such as 100 g / L to 260 g / L, 120 g / L to 220 g / L, or 140 g / L to 200 g / L. Bulk density can be measured according to ASTM D1513-05.
[0041] The resulting densified and optionally dried acetylene black generally has a particle size distribution. The particle size distribution may vary over a wide range. The particle size distribution may be measured by dynamic image analysis using a CAMSIZER X2 particle analyzer from Microtrac-Resch, Hanna, Germany, in accordance with ISO 13322-2. Typically, more than 85% by weight, such as 90% by weight or more, or 95% by weight or more, of the densified and optionally dried acetylene black has a particle size in the range of 0.1 mm to 2 mm. The densified and optionally dried acetylene black has a median particle size D of 0.2 mm or more, such as 0.4 mm or more, 0.6 mm or more, 0.8 mm or more, or 1.0 mm or more. v50 The densified and optionally dried acetylene black may have a median particle size D of 2.0 mm or less, e.g., 1.8 mm or less, 1.5 mm or less, or 1.2 mm or less. v50 The median particle size D of the densified and optionally dried acetylene black may be v50can range between any of the listed numerical values, such as a range of 0.2 mm to 2.0 mm, a range of 0.4 mm to 1.8 mm, or a range of 0.6 mm to 1.5 mm.
[0042] The densified and optionally dried acetylene black may have a fines content according to ASTM D1508-12(2017) of 15% by weight or less, e.g., 10% by weight or less, 8% by weight or less, 5% by weight or less, 3% by weight or less, or 1% by weight or less, based on the total weight of the acetylene black. Optionally, the method according to the invention may include a step of removing particles of a selected size, such as fines, from the densified and optionally dried acetylene black. Such removal may be achieved by any method known in the art, such as by passing through one or more screens having an appropriate mesh size.
[0043] The densified and optionally dried acetylene black may in particular be in the form of pellets. The pellets may have an average pellet crush strength of 20 g or less, such as 15 g or less, 10 g or less, or 8 g or less. The pellets may have an average pellet crush strength of 1 g or more, such as 2 g or more, 3 g or more, 4 g or more, or 5 g or more. The average pellet crush strength may range between any of the recited values, such as 1 g to 20 g, or 2 g to 10 g. The average pellet crush strength may be measured by ASTM D5230-00.
[0044] The method disclosed herein further comprises pulverizing the densified and optionally dried acetylene black, which may be as described above, to form a powdered acetylene black material according to the present invention. The pulverization of the densified acetylene black can be carried out by any means known in the art for forming a powder from a dense solid entity, such as pellets, granules or solid mass, such as grinding, crushing, grinding or a combination thereof. The pulverization, e.g., grinding the densified and optionally dried acetylene black, can be carried out using, for example, a hammer mill, a jaw crusher, a rotor mill, a ball mill, a knife mill, a mortar grinder, a cutting mill, a disk mill, a cross beater mill, a sieve assembly, or a combination thereof. The pulverization according to the present invention can be carried out in one or multiple steps, e.g., two, three or more steps, where the same or different pulverization means can be applied in the different pulverization steps. The densified and optionally dried acetylene black is typically ground or otherwise pulverized until a free-flowing, homogeneous powder is formed.
[0045] The powdered acetylene black material according to the present invention thus obtained can be characterized by its aggregate size distribution. The aggregate size distribution can be measured using a disk centrifuge photosedimentometer according to ISO 15825:2004. For example, the powdered acetylene black according to the present invention has a size distribution of D v50 The powdered acetylene black according to the present invention may have an aggregate particle size distribution of D 50 nm or more, for example, 75 nm or more, 100 nm or more, 200 nm or more, or 300 nm or more. v50 The powdered acetylene black according to the present invention may have an aggregate particle size distribution with a D between any of the recited values, such as 50 nm to 1000 nm, 100 nm to 500 nm, or 200 nm to 400 nm. v50 The aggregate size distribution may have the following structure:
[0046] The particles of the powdered acetylene black material of the present invention can have an irregular or non-spherical shape. The shape can be characterized, for example, by the aspect ratio, which is defined as the ratio of the smallest ferret diameter to the largest ferret diameter. The particles of the powdered acetylene black of the present invention can have, for example, an aspect ratio of less than 0.8, such as less than 0.6, less than 0.5, or less than 0.3. The aspect ratio can be determined from an electron microscope image, averaging over at least 50 particles.
[0047] The powdered acetylene black material prepared according to the method of the present invention is typically denser than the initial acetylene black from which it is produced. The powdered acetylene black material of the present invention can have a bulk density of, for example, at least 60 g / L, at least 70 g / L, at least 80 g / L, at least 90 g / L, or at least 100 g / L. The powdered acetylene black material of the present invention can have a bulk density of, for example, 160 g / L or less, such as 140 g / L or less, or 120 g / L or less. The bulk density of the powdered acetylene black material can range between any of the recited values, such as 60 g / L to 160 g / L, 70 g / L to 140 g / L, or 80 g / L to 120 g / L. Bulk density can be measured according to ASTM D1513-05. Without wishing to be bound by any theory, it is believed that the relatively high density of the powdered acetylene black material obtained by the process according to the present invention, possibly in combination with the irregular or non-spherical shape of the particles, may promote the dispersibility of the powdered acetylene black material and the formation of dispersions that are stable over extended periods of time and have favorable processing and / or application properties, such as reduced viscosity and / or improved electrical conductivity.
[0048] The process according to the present invention may therefore obtain a powdered acetylene black material having improved properties, such as in terms of dispersibility and processability, compared to the initial acetylene black used as starting material, while other properties may remain substantially unchanged. Thus, the powdered acetylene black material according to the present invention may have, for example, a specific surface area, OAN, COAN, acetone absorption number, ash content and / or chemical composition that corresponds or is comparable to that of the initial acetylene black. For example, the powdered acetylene black material according to the present invention may have a specific surface area, OAN, COAN, acetone absorption number, ash content, metal or iron content, carbon content, and / or sulfur content that are within ±30%, such as ±20% or ±10%, of the respective properties of the initial acetylene black used as starting material for its preparation.
[0049] Thus, the powdered acetylene black material of the present invention can have one or more or all of the properties described below.
[0050] The powdered acetylene black material of the present invention can be characterized by its specific surface area. 2 / g or more, e.g. 30m 2 / g or more, 40m 2 / g or more, 50m 2 / g or more, or 60m 2 The powdered acetylene black material can have a BET surface area of 200 m 2 / g or less, e.g. 180m 2 / g or less, 160m 2 / g or less, 140m 2 / g or less, 120m 2 / g or less, or 100m 2 The BET surface area of the powdered acetylene black material is preferably less than 20 m / g. 2 / g to 200m 2 / g, 40m 2 / g to 140m 2 / g, or 60m 2 / g to 100m2 The BET surface area can range between any of the recited values, such as 1 / g. The BET surface area measured can be measured by nitrogen adsorption according to ASTM D6556-19a.
[0051] Additionally or alternatively, the powdered acetylene black material can be characterized by its oil absorption number (OAN) measured according to ASTM D2414-19. The powdered acetylene black material can have, for example, an OAN of 500mL / 100g or less, such as 450mL / 100g or less, 400mL / 100g or less, 350mL / 100g or less, or 300mL / 100g or less. The powdered acetylene black material can have, for example, an OAN of 50mL / 100g or more, such as 100mL / 100g or more, 150mL / 100g or more, 200mL / 100g or more, or 250mL / 100g or more. The OAN of the powdered acetylene black material can range between any of the recited values, such as 50 mL / 100 g to 500 mL / 100 g, 100 mL / 100 g to 400 mL / 100 g, or 150 mL / 100 g to 300 mL / 100 g.
[0052] Further, in addition, or alternatively, the powdered acetylene black material can be characterized by a compressed sample oil absorption (COAN) measured according to ASTM D3493-19a. The powdered acetylene black material can have, for example, a COAN of 300 mL / 100 g or less, such as 250 mL / 100 g or less, 200 mL / 100 g or less, or 150 mL / 100 g or less. The powdered acetylene black material can have, for example, a COAN of 50 mL / 100 g or more, such as 100 mL / 100 g or more, 120 mL / 100 g or more, or 140 mL / 100 g or more. The COAN of the powdered acetylene black material can range between any of the listed values, such as 50 mL / 100 g to 300 mL / 100 g, or 100 mL / 100 g to 200 mL / 100 g.
[0053] Further, additionally or alternatively, the powdered acetylene black material may be characterized by an acetone absorption number measured according to Indian Standard IS12178-1987, test method A-6. Thus, the powdered acetylene black material may have, for example, an acetone absorption number of 5 mL / 5g or more, such as 10 mL / 5g or more, 15 mL / 5g or more, 25 mL / 5g or more, or 30 mL / 5g or more. The powdered acetylene black material may have, for example, an acetone absorption number of 100 mL / 5g or less, such as 80 mL / 5g or less, 70 mL / 5g or less, 60 mL / 5g or less, 50 mL / 5g or less, or 40 mL / 5g or less. The powdered acetylene black material may have an acetone absorption number in the range between any of the listed values, such as 5 mL / 5g to 100 mL / 5g, 15 mL / 5g to 80 mL / 5g, or 25 mL / 5g to 40 mL / 5g.
[0054] Additionally or alternatively, the powdered acetylene black material can be characterized by its chemical composition or purity, for example by its carbon content, sulfur content, iron content and / or ash content. For example, the powdered acetylene black material can have a carbon content of 90% by weight or more, for example 95% by weight or more, 98% by weight or more, preferably 99% by weight or more, more preferably 99.5% by weight or more, based on the total weight of the powdered acetylene black material. The sulfur content of the powdered acetylene black material can be, for example, 1% by weight or less, for example 0.5% by weight or less, 0.2% by weight or less, preferably 0.1% by weight or less, more preferably 0.05% by weight or less, based on the total weight of the powdered acetylene black material. The carbon content and sulfur content can be measured by quantitative elemental analysis. The powdered acetylene black material can have a low metal content, in particular a low iron content. The iron content of the powdered acetylene black material can be, for example, 1000 ppm or less, such as 500 ppm or less, 200 ppm or less, 100 ppm or less, 50 ppm or less, or 20 ppm or less, preferably 10 ppm or less, more preferably 5 ppm or less, based on the total weight of the powdered acetylene black material. The metal content or iron content of the powdered acetylene black material can be measured by inductively coupled plasma optical emission spectroscopy (ICP-OES). Furthermore, the powdered acetylene black material can have an ash content of 1 wt. % or less, for example 0.5 wt. % or less, 0.2 wt. % or less, preferably 0.1 wt. % or less, more preferably 0.05 wt. % or less, based on the total weight of the powdered acetylene black material. The ash content can be measured according to ASTM D1506-15.
[0055] The process according to the present invention therefore makes it possible to prepare powdered acetylene black materials having unique properties that are decoupled from the actual production of acetylene black from acetylene-containing feedstocks in a reactor, whilst retaining certain properties of conventional acetylene carbon black grades, making the replacement of these grades by the powdered acetylene black materials of the present invention more acceptable to customers.
[0056] The powdered acetylene black material can be advantageously processed using common powder processing means and can be easily used in formulations. The present invention therefore also relates to compositions comprising the above powdered acetylene black material. Such compositions typically comprise a dispersion of the powdered acetylene black in a carrier medium. As mentioned above, the advantages of the powdered acetylene black according to the present invention lie in its good dispersibility in the carrier medium, the remarkable stability, and the good processability and applicability of the resulting dispersion. Suitable carrier media include aqueous or organic solvent-based carrier media or plastic matrices.
[0057] As used herein, aqueous carrier medium refers to a carrier medium that contains more than 50% by weight, such as 70% by weight or more, 80% by weight or more, 90% by weight or more, or up to 100% by weight of water based on the total weight of the carrier medium. Organic solvent-based carrier medium refers to a carrier medium that contains more than 50% by weight, such as 70% by weight or more, 80% by weight or more, 90% by weight or more, or up to 100% by weight of organic solvent based on the total weight of the carrier medium. The type of carrier medium used depends on the type of each application and can vary widely. The carrier medium may contain water and / or one or more organic solvents. Organic solvents that can be used include, but are not limited to, alcohols, ketones, aldehydes, amines, esters, ethers, carboxylic acids, hydrocarbons, or mixtures or combinations thereof.
[0058] Likewise, all types of polymers or resin materials can be used as the plastic matrix in the composition according to the present invention, depending on the intended application.Non-limiting examples of useful resins and polymers that can be used in the present invention include olefin polymers such as polypropylene, polyethylene, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol resin, and cyclic olefin copolymer, natural rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, butyl rubber, acrylic rubber, ethylene-propylene rubber, ethylene-propylene terpolymer, ethylene-α-olefin copolymer rubber, silicone rubber, fluororubber, chloroprene rubber, hydrin rubber, and chlorosulfonated polyethylene rubber, vinyl chloride polymers such as polyvinyl chloride and ethylene-vinyl chloride copolymer, polystyrene, styrene-acrylonitrile copolymer, Examples of the resin include styrene-based polymers such as acrylonitrile-butadiene-styrene copolymers, acrylic polymers such as polymethyl methacrylate, polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyamides, polyacetals, and polycarbonates, fluororesins such as polyphenylene ether, polytetrafluoroethylene, and polyvinylidene fluoride, polyphenyline sulfide, liquid crystal polymers, thermoplastic polyamides, ketone resins, sulfone resins, phenyl resins, urea resins, melamine resins, alkyd resins, silicone resins, epoxy resins, urethane resins, polyvinyl esters, polyimides, furan resins, quinine resins, and mixtures, blends, and combinations thereof.
[0059] Depending on the type of application, further components can be used in formulating the composition according to the present invention. Those skilled in the art will select any such further components and their respective amounts according to the desired properties and / or use of the composition. Examples of such further components include, for example, oils and waxes, processing aids, rheology modifiers, pH adjusters, fillers, pigments, dyes, coupling agents, catalysts, accelerators, vulcanizing agents, activators, sulfur curing agents, antidegradants, antioxidants, stabilizers, biocides, and plasticizers. As described in more detail below, the compositions according to the present invention are useful, for example, for electrochemical applications, such as battery applications. Thus, for these applications, they may further comprise one or more electrochemically active components. The electrochemically active components may, for example, be common anode or cathode materials.
[0060] The composition according to the present invention can be prepared by a process comprising dispersing a powdered acetylene black material as disclosed herein in a carrier medium, such as an aqueous or organic solvent-based carrier medium or a plastic material as described above. Any additional components, such as those described above, can be added together with or separately from the powdered acetylene black material, if any. The resulting mixture can be optionally dried and / or cured.
[0061] The powdered acetylene black material according to the present invention can be compounded and dispersed in a carrier medium, such as an aqueous or organic solvent-based carrier medium or a plastic material as described above, using common mixing and blending equipment, for example, blenders, mixers, kneaders, single-screw or twin-screw extruders. The amount in which the powdered acetylene black material is used depends largely on the type of composition and the intended use, and will be selected by the skilled person according to their respective needs, based on similar formulations as conventional acetylene black.
[0062] As will be appreciated, the compositions according to the invention can be utilized in a variety of technical applications where acetylene black is generally appreciated for its properties, such as electrical and / or thermal conductivity, good dispersibility, and the formation of stable dispersions having good processing properties are desirable or beneficial.
[0063] The powdered acetylene black material of the present invention can, for example, impart electrical conductivity to compositions containing it and articles made therefrom. Thus, the powdered acetylene carbon black material of the present invention is particularly useful for battery applications, including, for example, primary batteries, secondary batteries, fuel cells or capacitors. Thus, the present invention is also directed to electrodes or other components of energy storage and / or conversion devices made from compositions comprising the powdered acetylene black material disclosed herein.
[0064] Furthermore, the powdered acetylene black material can also be used as an antistatic agent or as a conductive agent, for example in plastic materials and articles. Furthermore, the powdered acetylene black material of the present invention can be used to impart electrical and / or thermal conductivity to polymeric and rubber compounds, such as bladders for tire manufacturing. Thus, the present invention also provides a rubber or plastic article made from a composition comprising the powdered acetylene black material disclosed herein.
[0065] The powdered acetylene black of the present invention can therefore be advantageously used, for example, as an electrical conductor, antistatic agent, thermally conductive agent, reinforcing filler and / or colorant for the manufacture of electrodes and other components of energy storage and / or conversion devices, such as primary batteries, secondary batteries, fuel cells and capacitors, and / or for the manufacture of plastic articles made of a thermoplastic or thermosetting polymer or rubber matrix, such as tires, wires, cable sheaths, belts, hoses, shoe soles, rollers, heaters or bladders, and / or in coatings, paints or inks.
[0066] Having generally described the invention above, a further understanding can be obtained by reference to the following specific examples, which are provided herein for illustrative purposes only and are not intended to limit the invention, which rather is to be accorded the full scope of the appended claims, including any equivalents thereof. EXAMPLES
[0067] All parts and percentages given throughout the examples are by weight unless otherwise specified.
[0068] Applied methods for characterization of acetylene black The BET specific surface area was measured by nitrogen adsorption according to ASTM D6556-19a.
[0069] Oil absorption (OAN) was measured according to ASTM D2414-19.
[0070] The oil absorption (COAN) of the pressed samples was measured according to ASTM D3493-19.
[0071] Carbon and sulfur contents were determined by quantitative elemental analysis using an automatic elemental analyzer (vario EL cube elemental analyzer from Elementor Analysis Systems) according to DIN 51732-2014-07.
[0072] Total metal content, including iron content, was measured by ICP-OES using a Prodigy7 instrument from Teledyne Lehman Labs, Massachusetts, USA.
[0073] Ash content was measured according to ASTM D1506-15.
[0074] Moisture content was measured according to ASTM D1509-95.
[0075] Bulk density was measured according to ASTM D1513-05.
[0076] Acetylene Black Material Acetylene black commercially available from Orion Engineered Carbon Corp. (referred to herein as Acetylene Black A) having the properties set forth in Table 1 below was used as the starting material for preparing the densified or powdered acetylene black materials described below and was used as the reference material.
[0077] [Table 1]
[0078] Preparation of pelletized acetylene black material (acetylene black B) The carbon black starting material was pelletized using a heated ring-bed mixer granulator RMG300 available from Amixon GmbH (Paderborn, Germany) equipped with a rotating mixer shaft with pins. The starting material was continuously fed to the granulator by a gravimetric feeder at a rate of 70-75 kg / h. Demineralized water below 70°C was continuously injected through a pressurized spray nozzle at a rate of 180 L / h. The rotating mixer shaft of the granulator rotated at a speed of 350 rpm and the temperature of the RMG300 was set to greater than 32°C and less than 75°C.
[0079] The resulting pellet material was then dried in a natural gas fired rotary dryer with a combustion chamber temperature >550°C and a carbon black bed temperature at the dryer exit of <150°C.
[0080] Selected properties of the thus obtained dry pelletized acetylene black material (designated Acetylene Black B) are summarized in Table 2 below.
[0081] Preparation of the powdered acetylene black material according to the present invention (acetylene black C) from pelletized acetylene black (acetylene black B) The pelletized acetylene black B was ground to produce a powdered acetylene black according to the invention, designated acetylene black C. The grinding was carried out in a cross-beater mill of the type "Pulverisette 1" manufactured by Fritsch (Idar-Oberstein, Germany) applying 2850 rpm and a stainless steel screen size of 0.25 mm.
[0082] Selected properties of the thus obtained micronized acetylene black material (designated Acetylene Black C) are also summarized in Table 2 below.
[0083] [Table 2]
[0084] From Table 2, in comparison with Table 1, it can be seen that the properties of the acetylene black starting material can be almost retained by the preparation method of the present invention, while a powdered acetylene black material with higher density is obtained compared with the acetylene black starting material.
[0085] Preparation of electrode formulations using acetylene black A-C A dry premix was prepared by adding 3.5 g of Solef5130 (Solvay) PVDF polymer, 93 g of Lithium-Nickel-Manganese-Cobalt-Oxide NMC532 (BASF). 3.5 g of each acetylene black material (acetylene black A, B, or C, see Table 3 below) was placed in the mixing vessel of a double planetary mixer, FMPE HM2P-03, Buehler Technologies, Ratingen, Germany. The composition was mixed in the double planetary mixer for 4 minutes at room temperature at a speed of 20 rpm.
[0086] The premixes were then dispersed in an organic solvent in a two-step procedure: First, 40 g of N-methyl-2-pyrrolidone (NMP, analytical purity ≧99.5% provided by VWR Chemical Company) was added to 100 g of each premix, which was then mixed in a double planetary mixer at 40 rpm for 10 minutes, followed by mixing at 60 rpm for 20 minutes. An additional 5 g of NMP was then added to the mixture, and the composition was mixed in a double planetary mixer at 60 rpm for an additional 20 minutes to obtain an electrode paste.
[0087] The viscosity of the resulting electrode paste was evaluated using a rheometer MCR302 from Anton Paar (Ostfildern-Scharnhausen, Germany). The viscosity was measured from 0 to 500 s at 20 °C. -1 The viscosity was measured at a shear rate of 200 s and the plate gap was 0.5 mm. -1 The viscosities at shear rates of 100-1500 nm are reported in Table 3 below.
[0088] Preparation of electrode films and measurement of electrical resistivity Electrode films were prepared from the prepared electrode paste (a) immediately after preparation, (b) after 3 hours aging, and (c) after 24 hours aging. Cathode films were prepared according to the following procedure. An aluminum foil with a thickness of 20 μm was applied on a coater (K-Control Coater manufactured by TQC Sheen). Then, each electrode paste without air bubbles was coated on the aluminum foil, and the layer thickness was adjusted using a doctor blade. The coated electrodes were dried in a vacuum oven at 100° C. for 3 hours. The film thickness of the resulting electrode layer was 50 μm. The electrical resistance of the resulting coated electrodes was measured with a Hioki RM3543 Resistance HiTESTER using coin cell samples punched from the dried coating on the Al foil. The average value of conductivity was calculated from six coins with a diameter of 1.4 mm from the same coating and reported in Table 3 below.
[0089] [Table 3]
[0090] As can be seen from Table 3, the paste formed using the acetylene black material according to the present invention (Example 3) showed a reduced viscosity compared to the paste containing the commercial reference material (Comparative Example 1) or the paste derived from pelletized acetylene black (Comparative Example 2), indicating better dispersion of the acetylene black according to the present invention in the electrode paste and favorable processing properties. Furthermore, the electrode film obtained from the powdered acetylene black material according to the present invention (Example 3) showed a significantly lower electrical resistivity than that obtained from the commercial reference material (Comparative Example 1) or from pelletized acetylene black (Comparative Example 2). The obtained electrode resistivity was stable and, in contrast to the comparative examples, did not increase significantly upon storage of the electrode paste for times up to 24 hours, indicating an improved stability of the dispersion formed using the powdered acetylene black material according to the present invention.
Claims
1. A method for producing a powdered acetylene black material, comprising the steps of: Providing an initial acetylene black; densifying the initial acetylene black provided to form a densified acetylene black; and pulverizing the densified acetylene black to form a powdered acetylene black material.
2. 2. The method of claim 1, wherein densifying the initial acetylene black comprises pelletizing the initial acetylene black to form pelletized acetylene black.
3. 3. The method of claim 2, wherein the initial acetylene black is wet pelletized using an aqueous medium.
4. 3. The method according to claim 1 or 2, comprising using at least one additive and / or polymer in the presence of a liquid medium and / or in the dry state in the step of densifying the initial acetylene black.
5. 3. The method according to claim 1 or 2, wherein the densification step is carried out using an agitation granulator.
6. 3. The method according to claim 1 or 2, wherein the densified acetylene black has a bulk density of at least 100 g / L, measured according to ASTM D1513-05.
7. 3. The method of claim 1 or 2, wherein the step of pulverizing the densified acetylene black comprises grinding the densified acetylene black.
8. 3. The method of claim 1 or 2, further comprising degassing the initial acetylene black prior to the densification step and / or further comprising drying the acetylene black.
9. A powdered acetylene black material obtained by the method according to claim 1.
10. 10. The powdered acetylene black material according to claim 9, having one or more or all of the following: A bulk density of at least 60 g / L as measured in accordance with ASTM D1513-05; 20-200m measured according to ASTM D6556-19a 2 / g BET surface area, an oil absorption (OAN) of 100-500 mL / 100 g as measured according to ASTM D2414-19; Acetone absorption of 15-80 mL / 5 g as measured according to Indian Standard IS 12178-1987, test method A-6; A carbon content of at least 99.0% by weight, a sulfur content of less than 0.1% by weight; an iron content of less than 1,000 ppm, and / or Ash content less than 0.1% by weight as determined according to ASTM D1506-15.
11. A composition comprising the powdered acetylene black material of claim 9.
12. The composition of claim 11 further comprising at least one electrochemically active component.
13. 13. An electrode or other component of an energy storage and / or conversion device made from the composition of claim 11 or 12.
14. 13. A rubber or plastic article made from the composition of claim 11 or 12.
15. Use of the powdered acetylene black material according to claim 9 or 10 as an electrical conductor, antistatic, thermally conductive, reinforcing filler and / or colorant for the manufacture of electrodes and other components of energy storage and / or conversion devices, and / or for the manufacture of plastic articles made of a thermoplastic or thermoset polymer or rubber matrix, and / or in coatings, paints or inks.